The Cohesion’s Elements of Education Articles in Kompasiana - Fathurrohman Gala Sanca; Erna Megawati; Azhari Ikhwati (Universitas Indraprasta PGRI, 2021)
The purpose of this study is to describe the kind of grammatical and lexical cohesion that used in education articles written by Syarifudin Yunus. The method that used in this study is qualitative descriptive method. Data source that used in this study are 24 education articles written by Syarifudin Yunus at Kompasiana.com web page in 2019 until 2020 year range. Technic that used in this study is basic technique of agih method or also called the BUL technique (For Direct Elements). The results of this study showed that there are four aspects of grammatical cohesions. The finding percentage of grammatical cohesion of this study are 54.4% conjunctions aspect, 35.4% references aspect, 6.1% substitutions aspect, and 4.1% ellipsis aspect. Besides, there are six lexical cohesion that found in this study. The percentage of lexical cohesions in this study are 63.5% repetition aspects, 14% equivalency aspects, 8.8% collocation aspects, 7.2% synonym aspects, 3.8% hyponyim aspects, and 2.7% antonym aspects. This study can be implicated for Indonesian language learning at junior high school and senior high school.Keywords: Grammatical cohesion; lexical cohesion; discourse.